Alvin Hansen and the Interactions between the Multiplier Analysis and the Principle of Acceleration - Samuelson, Paul A. (The Review of Economics and Statistics, 1959)
Paul A. Samuelson, Alvin Hansen and the Interactions between the Multiplier Analysis and the Principle of Acceleration, The Review of Economics and Statistics, Vol. 41, No. 2, Part 1 (May, 1959), pp. 183-184